SAT0025 Shift in Genetic Composition of an IL-32 Promoter Polymorphism Resuls in a Higher Cytokine Production in RA Patients. (9th June 2015) - Damen, M.; Heinhuis, B.; Tweehuysen, L.; den Broeder, A.; Netea, M.; Popa, C.; Joosten, L.
Abstract : Background: IL-32 is a cytokine that can be spliced into various isoforms with different potency and can induce pro-inflammatory cytokines like IL-6, IL-1β and TNFα.[1] IL-32 was found to play a role in the pathogenesis of rheumatoid arthritis (RA). High expression levels of IL-32 were found in RA synovial tissue biopsies, which correlated with synovial presence of TNFα.[2] Expression of IL-32 splice variants might be regulated by promoter single nucleotide polymorphisms (SNPs), however functional implications of these SNPs are still unknown in RA patients. Objectives: To investigate the effects of an IL-32 promoter SNP (rs4786370) on the expression of IL-32 splice variants in healthy individuals and RA patients and the genetic composition within these groups. Determine whether differences in genotype result in changes in the immune response to pro-inflammatory cytokines and Pathogen-associated molecular patterns (PAMPs) in control versus RA patients. Methods: Peripheral blood mononuclear cells (PBMCs) from healthy individuals and RA patients were stimulated with various pro-inflammatory cytokines and PAMPs. Next, mRNA levels of different splice variants of IL-32 were determined by quantitative PCR and genotype for the IL-32 polymorphism was determined by taqman assays. Additionally, pro-inflammatory cytokines were measured in supernatants by ELISA. Results: The expression of the most potent splice variant IL-32γ was higher at basal level for the TT-genotype compared to the CC-genotype in both healthy individuals and RA patients. Furthermore, significantly higher levels of pro-inflammatory cytokines such as IL-6 and IL-8 were found in healthy individuals with the TT-genotype. In line with this, in a large cohort of RA patients stimulation with PAMPs also showed a higher immune response linked to the TT-genotype. Remarkably, within the RA cohort the allele frequency of TT was increased with 5.9% whereas the allele frequency of CC decreased with 5% compared to the allele frequencies in the European population (HapMap data). The percentage of heterozygous individuals stayed similar. Conclusions: A polymorphism in the promoter region of IL-32 results in higher IL-32γ mRNA expression in people with the TT-genotype. This genotype is also linked with a higher cytokine production in PBMCs from healthy individuals, exposed to IL-1 or poly I:C. Furthermore, this genotype seems to occur more frequently in RA patients. Future studies should investigate whether this observation is of clinical relevance, i.e. determining the level of disease activity or response to anti-rheumatic drugs. References: Dinarello, C.A. and S.H. Kim, IL-32, a novel cytokine with a possible role in disease. Ann Rheum Dis, 2006. 65 Suppl 3: p. iii61-4. Joosten, L.A., et al., IL-32, a proinflammatory cytokine in rheumatoid arthritis. Proc Natl Acad Sci U S A, 2006. 103(9): p. 3298-303. Disclosure of Interest: None declared